2011
DOI: 10.1007/s10194-011-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Classification and clinical features of headache patients: an outpatient clinic study from China

Abstract: This study aimed to analyze and classify the clinical features of headache in neurological outpatients. A cross-sectional study was conducted consecutively from March to May 2010 for headache among general neurological outpatients attending the First Affiliated Hospital of Chongqing Medical University. Personal interviews were carried out and a questionnaire was used to collect medical records. Diagnosis of headache was according to the International classification of headache disorders, 2nd edition (ICHD-II).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
43
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 24 publications
13
43
7
Order By: Relevance
“…The frequency of CDH as a percentage of all headache patients ranged from 23% to 79% (mean 43%). The mean frequency of CM as a percentage of CDH cases was 46%, with the lowest value (4.7%) again from a Chinese study (54). In patients with CM, the frequency of MOH or medication overuse was 28-75% (mean 54%) ( Table 2).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The frequency of CDH as a percentage of all headache patients ranged from 23% to 79% (mean 43%). The mean frequency of CM as a percentage of CDH cases was 46%, with the lowest value (4.7%) again from a Chinese study (54). In patients with CM, the frequency of MOH or medication overuse was 28-75% (mean 54%) ( Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…Eleven studies reported the frequency of CDH, which ranged from 23% (54,61) to 79% (68) of patients with headache. The CDH frequency was below 30% in four studies(54,61,62,71), one of which used alternative criteria(20,71), 36-39% in three studies from Malaysia…”
mentioning
confidence: 98%
“…The prevalence of headache in the adult population is 46%. Tension-type headache (43%) and migraine (11%) are types of headaches that most frequently affect adults (1).…”
Section: Introductionmentioning
confidence: 99%
“…5(2), 1458-1461 1459 Unfortunately, chronically affected migraine patients are more likely, than other headache patients, to overuse analgesics. [4] Each year, 2.5% of patients with episodic migraine (EM) develop new-onset chronic migraine. [5] Overuse of analgesics among patients with episodic migraine put them at great risk of getting transformed migraine, progression from episodic migraine(<15days/month) to chronic migraine.…”
Section: Issn: 2320-5407mentioning
confidence: 99%